2008
DOI: 10.1099/vir.0.2008/002352-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional studies of per os infectivity factors of Helicoverpa armigera single nucleocapsid nucleopolyhedrovirus

Abstract: A combined functional investigation on the four per os infectivity factors (PIFs) of Helicoverpa armigera single nucleocapsid nucleopolyhedrovirus (HearNPV) was conducted in this study. HearNPV bacmids with deletions of p74 (Ha20), pif1 (Ha111), pif2 (Ha132) and pif3 (Ha98) were constructed individually by homologous recombination in Escherichia coli cells. Repaired bacmids with respective pifs were also constructed. Western blot analyses revealed that all four PIFs were structural components of the envelope o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 36 publications
(40 reference statements)
2
60
0
2
Order By: Relevance
“…We previously demonstrated that OBs produced by coinfecting insects with mixtures of complete (ϳ75%) and defective (ϳ25%) genotypes were ϳ2.5-fold more infectious than OBs comprising the complete genotype alone. The absence of PIF1 or PIF2 results in the complete loss of peroral infectivity in other NPVs (17,31,32,36,43). The lack of per os infectivity of both C and D genotypes was clearly due to the deletion of pif1 and pif2.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously demonstrated that OBs produced by coinfecting insects with mixtures of complete (ϳ75%) and defective (ϳ25%) genotypes were ϳ2.5-fold more infectious than OBs comprising the complete genotype alone. The absence of PIF1 or PIF2 results in the complete loss of peroral infectivity in other NPVs (17,31,32,36,43). The lack of per os infectivity of both C and D genotypes was clearly due to the deletion of pif1 and pif2.…”
Section: Discussionmentioning
confidence: 93%
“…The PIF proteins comprising PIF1, PIF2, and the recently identified PIF3 (Ac115) are found at low quantities in the envelopes of ODVs (1,9,17,25,31,43), together with an addition infection factor, P74 (10). This low level of expression is due to the weakness of its promoter, at least in the case of pif1 (17,32).…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding per os infectivity factors (pifs) and p74 structural proteins are common to all sequenced nudiviruses and baculoviruses, and they are essential for oral infectivity (Kuzio et al, 1989;Kikhno et al, 2002;Pijlman et al, 2003;Ohkawa et al, 2005;Song et al, 2008). These genes are known or presumed to encode envelope proteins typical of the occlusion-derived virus phenotype, which are important for the entry process into the midgut epithelial cells (Slack & Arif, 2007).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Moreover AcMNPV PIF-6 and HearNPV PIF-4 were shown to be ODV components by Western blotting. The function of the seven PIFs was demonstrated by knockout experiments mainly in HearNPV and AcMNPV (Fang et al, 2006;Huang et al, 2012;Nie et al, 2012;Song et al, 2008;Sparks et al, 2011;Xiang et al, 2011). The results of knockout experiments and the identification of PIFs in different baculoviruses by different approaches confirmed the conservation of these proteins and validated the feasibility of MS approaches.…”
Section: Proteins Encoded By Baculovirus Core Genesmentioning
confidence: 99%